2008
DOI: 10.1016/j.mod.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected activities of Smad7 in Xenopus mesodermal and neural induction

Abstract: Neural induction is widely believed to be a direct consequence of inhibition of BMP pathways. Because of conflicting results and interpretations, we have re-examined this issue in Xenopus and chick embryos using the powerful and general TGFbeta inhibitor, Smad7, which inhibits both Smad1- (BMP) and Smad2- (Nodal/Activin) mediated pathways. We confirm that Smad7 efficiently inhibits phosphorylation of Smad1 and Smad2. Surprisingly, however, over-expression of Smad7 in Xenopus ventral epidermis induces expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…The coding regions of chick Calreticulin (CALR), zebrafish Calreticulin (calr) (Rubinstein et al, 2000), human Calnexin (CANX) (kind gift from Marek Michalak (Vassilakos et al, 1998), Xenopus truncated BMP receptor (Suzuki et al, 1994), cSmad6 (a kind gift from P Szendro and G Eichele) (de Almeida et al, 2008, Yamada et al, 1999), cChordin (Streit et al, 1998) and xSmad7 (Casellas and Brivanlou, 1998, de Almeida et al, 2008) were each cloned into pCAβ-IRES-GFP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coding regions of chick Calreticulin (CALR), zebrafish Calreticulin (calr) (Rubinstein et al, 2000), human Calnexin (CANX) (kind gift from Marek Michalak (Vassilakos et al, 1998), Xenopus truncated BMP receptor (Suzuki et al, 1994), cSmad6 (a kind gift from P Szendro and G Eichele) (de Almeida et al, 2008, Yamada et al, 1999), cChordin (Streit et al, 1998) and xSmad7 (Casellas and Brivanlou, 1998, de Almeida et al, 2008) were each cloned into pCAβ-IRES-GFP.…”
Section: Methodsmentioning
confidence: 99%
“…Although BMP inhibition is absolutely required for neural induction to take place (De Robertis and Kuroda, 2004, Harland, 2000, Hemmati-Brivanlou and Melton, 1997, Linker and Stern, 2004), it is increasingly clear that other signals are also required (Stern, 2005). Known additional factors include FGFs, IGFs and Wnt inhibition, but even a combination of all of these factors is insufficient to mimic the effect of a node graft to the area opaca in the chick (de Almeida et al, 2008, Linker and Stern, 2004), suggesting that other factors are also involved.…”
Section: Introductionmentioning
confidence: 99%
“…It would be worthwhile to determine whether Zeb2 also recruits Smad7 to inhibit BMPSmad signalling during neural induction. Indeed, Smad7 has been shown to promote neural induction in the Xenopus and chick embryos (Bhushan et al, 1998;Casellas and Brivanlou, 1998;Chang and Harland, 2007;de Almeida et al, 2008). Weng et al (2012) demonstrated that Zeb2 not only acts as a transcriptional activator and repressor in the same cell, but that the transcriptional modulation of various differentiation regulators by Zeb2 is stage-dependent.…”
Section: Zeb2 In Glial Developmentmentioning
confidence: 99%
“…Several lines of evidence implicate BMP inhibition as an essential step in neural induction (de Almeida et al, 2008, Harland, 2000, Hemmati-Brivanlou and Melton, 1997, Linker et al, 2009, Linker and Stern, 2004, Marchal et al, 2009, Reversade et al, 2005, Stern, 2006, Vonica and Brivanlou, 2006. However chick epiblast cells cannot respond to BMP inhibitors unless they have previously been exposed for at least 5 hours to other signals from the organizer Stern, 2004, Streit et al, 1998).…”
Section: Introductionmentioning
confidence: 99%